The Association Between Base-Area Social and Economic Characteristics and Airmen's Outcomes - Sarah O. Meadows,, Laura L. Miller, Jeremy N. V. Miles (RAND Corporation, 2014)
The views expressed are those of the authors and do not reflect the official policy or position of the Department of the Air Force. A large body of work in sociology and related fields has found that neighborhood characteristics can have an impact on health and well-being beyond individual-level characteristics. Although members of the military and their families move more frequently than the average citizen and, in the case of active-duty service members, have the opportunity to live on a military installation rather than in the general community, the quality and characteristics of the areas where they live can also affect their, and their families’, well-being. Military base services in disadvantaged neighborhoods can compensate for the lack of resources needed to be safe, secure, and healthy and to thrive. Air Force Services asked the RAND Corporation to enhance its ability to tailor support for Airmen and their families through analysis of the relevance of neighborhood, or area, characteristics of the areas surrounding major Air Force installations in the United States. We applied established social indicators and neighborhood studies methodology to (1) score 66 major Air Force installations in terms of their areas’ social and economic characteristics and (2) estimate the association between those scores and self-reported Airman outcomes related to health and well-being, military and neighborhood social cohesion, ratings of neighborhood resources, use of on-base resources, satisfaction, and career intentions. The objective was to identify which areas may have greater need for Air Force resources, so that Air Force Services can enhance its programming in those areas and consider this need when making budget decisions. This document reports the results of that analysis. No special expertise is required of readers. The research reported here was sponsored by the Air Force Office of Airman and Family Services (AF/A1SA) and conducted within the Manpower, Personnel, and Training Program of RAND Project AIR FORCE. It was an update and extension of an earlier RAND-sponsored proof-of-concept study using data from 2000–2003, published in Exploring the Association Between Military Base Neighborhood Characteristics and Soldiers’ and Airmen’s Outcomes by Sarah O. Meadows, Laura L. Miller, Jeremy N. V. Miles, Gabriella C. Gonzalez, and Brandon Dues (TR-1234-RC/A/AF), 2013.